High pressures and asymmetrical stresses in the scoliotic disc in the absence of muscle loading. - Meir, A; Fairbank, J; Jones, D; McNally, D; Urban, J (2007)
BACKGROUND: Loads acting on scoliotic spines are thought to be asymmetric and involved in progression of the scoliotic deformity; abnormal loading patterns lead to changes in bone and disc cell activity and hence to vertebral body and disc wedging. At present however there are no direct measurements of intradiscal stresses or pressures in scoliotic spines. The aim of this study was to obtain quantitative measurements of the intradiscal stress environment in scoliotic intervertebral discs and to determine if loads acting across the scoliotic spine are asymmetric. We performed in vivo measurements of stresses across the intervertebral disc in patients with scoliosis, both parallel (termed horizontal) and perpendicular (termed vertical) to the end plate, using a side mounted pressure transducer (stress profilometry) METHODS: Stress profilometry was used to measure horizontal and vertical stresses at 5 mm intervals across 25 intervertebral discs of 7 scoliotic patients during anterior reconstructive surgery. A state of hydrostatic pressure was defined by identical horizontal and vertical stresses for at least two consecutive readings. Results were compared with similar stress profiles measured during surgery across 10 discs of 4 spines with no lateral curvature and with data from the literature. RESULTS: Profiles across scoliotic discs were very different from those of normal, young, healthy discs of equivalent age previously presented in the literature. Hydrostatic pressure regions were only seen in 14/25 discs, extended only over a short distance. Non-scoliotic discs of equivalent age would be expected to show large centrally placed hydrostatic nuclear regions in all discs. Mean pressures were significantly greater (0.25 MPa) than those measured in other anaesthetised patients (<0.07 MPa). A stress peak was seen in the concave annulus in 13/25 discs. Stresses in the concave annulus were greater than in the convex annulus indicating asymmetric loading in these anaesthetised, recumbent patients. CONCLUSION: Intradiscal pressures and stresses in scoliotic discs are abnormal, asymmetrical and high in magnitude even in the absence of significant applied muscle loading. The origin of these abnormal stresses is unclear.